OPERATED ORGAN AND REPRODUCTIVE PROBLEMS - Безнощенко, Галина Борисовна; Кравченко, Елена Николаевна; Цыганкова, Ольга Юрьевна; Кропмаер, Кирилл Петрович; Кузьменко, Елена Валентиновна (Mother and Baby in Kuzbass, 2020)
A comparative analysis of the evaluation of the main parameters of the functional state of the ovaries in dynamics was carried out in 86 women after organ-preserving laparoscopic operations for benign ovarian tumors. The presented data showed the dependence of the treatment results on the initial anatomical and functional changes in the reproductive sphere, the state of the neuroendocrine system and the adequacy of the operative effect and rehabilitation measures.